Towards commercial federalism: Retail regulation in Italy (Ciudades, 2018)
The reform of the retail sector in 1998 and a specific federalist modification of the Italian Constitution in 2001 have driven the Regions to approve different Acts for retail regulations, that are closely related to territorial development. Some Regions, as Piemonte, Emilia Romagna and Lombardia, have tried to introduce criteria of programming new retail locations, mainly largest ones, connected to territorial characteristics. This approach introduces innovative tools to evaluate retail repercussions on the sites. Other Regions have continued with the traditional tools for quantitative control of retail areas, promoted by private developers, often foreign ones, who can act in the market in nearly monopolistic conditions. The Lombardia Region with its more recent retail programming triennial Act (2006-2008) has introduced the objective “zero impact” for new retail development, containing the suburban land use and reusing dismantled areas. Other policies are foreseen specifically planned to different contexts even experimenting models of unitary management of local retail planning.
Keywords: retail regulations; territorial policies